Budaya Organisasional, Kepuasan Kerja, dan Komitmen Organisasional dalam Meningkatkan Perilaku Inovatif - Dahri, Nur Wahyunianti; Aqil, Muhammad (Universitas Muhammadiyah Yogyakarta, 2018)
Human resources is a very important factor as a driver in the face of global current era. The competitiveness of an organization depends on human resources owned. Particularly associated with either organizational commitment and innovative behavior. This research would like to see more activities and responsibilities in developing organizational commitment, organization culture, and job satisfaction to improving employee's innovative behavior.